Video-activism and the citizenship documentary image - Porto Reno, Denis [UNESP] (Centro Int Estudios Superiores Comunicacion Amer Latina-ciespal, 2015)
Understanding the contemporary media ecology is a challenge for researches in the communication. In this complex communication diversity, the video-activism and the popular documentary film stand out for the capacity of construction of the public opinion. Thinking about video-activism implies a review of what it means. It is, basically, any audiovisual product that aims to change society. This paper offers a resultant reflection of a study on activist videos and build of documentary images. The aim is to build basis for further research on the subject, from the categories presented here.
Keywords: communication; documentary; video-activism; citizenship